Investigate of the Effect of Width Defect on Eddy Current Testing Signals Under Different Materials - Faraj, Moneer A.; Abdalla, Ahmed N.; Fahmi, Samsuri; Damhuji, Rifai; Kharudin, Ali (Informatics Publishing Limited, 2017)
Objectives: Non-Destructive Evaluation (NDE) is the inspection of an object to determine its properties without destroying its usefulness. It is used, for example, to detect cracking in steam generator tubing in nuclear power plants and aircrafts. Eddy Current NDE is a commonly used method of NDE. This study creates a sample calibration block with different materials and investigates the effect of width defects in these materials on the Eddy Current signal. Method/Statistical: The materials of the artificial defect block are mild steel, brass and copper with dimensions of 260 mm (length) × 30 mm (width) × 10 mm (height). A total of 12 artificial defects are located 20 mm parallel to the length of the block. The distance of the defect is located in between 1 mm up to 2.5 mm from the surface of the artificial defect block. A weld probe was used to inspect the block. The wire cut machines were utilized to add defects to the sample block. Findings: Results prove that the deviation of Eddy Current Testing measurement was influenced by the width and material of the objective. Application/Improvement: The results showed that the signal of the Eddy Current was affected by the size of the defect and the type of specimen.